Effect of Honeycomb Core on Free Vibration Analysis of Fiber Metal Laminate (FML) Beams Compared to Conventional Composites. (1st April 2021) - Ameri, Behnam; Moradi, Morteza; Talebitooti, Roohollah
Abstract: According to the different higher-order deformation beam theories, the current survey is related to the fundamental frequency analysis of composite beams using the Rayleigh-Ritz method. Different types of materials, including isotropic, fiber-reinforced orthotropic composites, and FML hybrid composites in the presence and the absence of honeycomb core, have been selected. In this theory, the material property as well as the thickness of each layer can be changed, and the effect of various boundary conditions, lay-up configurations, and slenderness ratios of the beams have been discussed. To verify the obtained theoretical results, the FML beam with [Al/0/90/90/0/Al] lay-up pattern was fabricated by hand lay-up technique and subjected to Clamped-Free boundary condition. Accordingly, the free vibration experimental data confirmed the results which were obtained by the different theories. The results show that by changing the reinforced composite beam to the FML beam, the natural frequencies experience a drop by 37%, 43%, and 43% for slenderness ratios of 5, 20, and 100, respectively. This level of descent for transferring from reinforced composite sandwich beam to the FML sandwich beam is about 24%, 37%, and 37.5%, respectively.